Bloch-Type Spaces of Minimal Surfaces. (1st November 2018) - He, Guanghua; Fu, Xi; Zhu, Hancan
Abstract : We study Bloch-type spaces of minimal surfaces from the unit diskD intoR n and characterize them in terms of weighted Lipschitz functions. In addition, the boundedness of a composition operatorC ϕ acting between two Bloch-type spaces is discussed.